Design of a Website-Based Goods Inventory Information System at the Grocery Store - Aldo Nicholas; Haris Yuana; Rahmat, Mohammad Faried (LPPM Telkom University Surabaya, 2025)
This research aims to design and build a website-based inventory information system at the Dewi Grocery Store. The problem currently faced by stores is that capturing and managing inventory data is still manual, causing problems such as difficulty monitoring stock, recording errors and making old reports. The research method used is Agile Methods, consisting of requirements, design, implementation, verification and maintenance. System design using Laravel, Visual Studio Code, MySQL, XAMPP, Draw.io, and Whimsical. The research result is a website-based inventory information system application that can help the Dewi Grocery Store manage inventory data effectively and efficiently. The sales inventory system is functional and user-friendly, making it a valuable tool for Dewi Grocery Store to effectively manage sales inventory and provide accurate reports. The application has category management features, item data, sales, and report creation, as well as prediction features to help shop owners make decisions. The results of black box, expert, and user testing show the application is worthy of use with scores of 94%, 76%, and 83 %, respectively.